2021
DOI: 10.1051/e3sconf/202126901010
|View full text |Cite
|
Sign up to set email alerts
|

A review on the current condition and control of campus noise pollution in central region of China

Abstract: With the increasing public attention to environmental protection, the control of pollution has become a joint goal of human. As one of the four major environmental pollutions, noise pollution seriously affects the normal study, work and health of teachers and students in schools, hence becoming an environmental issue of general concern in modern society. At present, the research and prevention of noise in colleges and universities are still in the initial stage in China. In addition, there are few noise studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Ou et al (2021) believed that noise pollution seriously affects the normal study, work and health of teachers and students in schools while monitory noise pollution is six universities in China. The study concludes that noise pollution has become a more and more common social problem around students and teachers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Ou et al (2021) believed that noise pollution seriously affects the normal study, work and health of teachers and students in schools while monitory noise pollution is six universities in China. The study concludes that noise pollution has become a more and more common social problem around students and teachers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The noise pollution was attributed to rapid urbanization and industrialization associated with high number of automobiles, generating plants, industries, and marketing strategies using mobile advertisement vans and mobile vendors, and conversion of residential areas to business and artisanal outfit. Ou et al (2021) believed that noise pollution seriously affects the normal study, work and health of teachers and students in schools while monitory noise pollution is six universities in China. The study concludes that noise pollution has become a more and more common social problem around students and teachers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Long-term exposure to a noisy environment not only leads to a severe decline in attention 1 but also causes mental and physical health problems. [2][3][4] Investigations in schools and residential areas in China have confirmed that public transportation and cars are the main sources of urban traffic noise, [5][6][7][8] and that the sound energy is concentrated at low-and middle-frequencies (0-2000 Hz). [9][10][11] Noise barriers are one of the most effective measures for alleviating traffic noise.…”
Section: Introductionmentioning
confidence: 99%